Investigation of the Flow Behaviour of Martensitic Steel at Elevated Temperatures Via Uniaxial Tensile Tests - N. Sen; T. Civek; O. Elkoca; E. Çevik (Archives of Metallurgy and Materials)
In recent years, advanced high strength steels have been the main choice of automobile manufacturers due to their excellent strengths and decent formability. In this study, the forming behaviour of a martensitic steel (MART 1200) at elevated temperatures, where higher formability and an acceptable strength can be achieved, has been investigated. For this purpose, tensile test experiments have been conducted at room temperature, 175°C, 275°C, 375°C and 475°C in two different strain rates (0.005 s–1, 0.05 s–1). The flow behaviour, elongation capacity, strain rate sensitivity, strain hardening and strain hardening rate of MART1200 have been investigated and fracture surfaces and microstructures have been examined by scanning electron microscope. It has been shown that the strain rate sensitivity of MART1200 increases significantly after 275°C and, for the higher strain rate, a significant improvement up to 80% in the elongation capacity has been achieved in return for a 19% strength reduction at 375°C.